2019
DOI: 10.1055/a-0835-6671
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Pharmacokinetics of Standardized Extract of Centella asiatica (ECa 233) Capsules in Healthy Thai Volunteers: A Phase 1 Clinical Study

Abstract: The aim of this study was to investigate the safety and pharmacokinetic profiles of a newly developed, standardized extract of Centella asiatica (ECa 233) capsule in healthy Thai volunteers. This study was designed as an open-labeled, 2-sequence dosage, single- and repeated-dose study investigated under fasting conditions. Plasma concentrations of the parent compounds and their relative acid metabolites were measured and pharmacokinetic parameters were calculated using noncompartmental analysis. Tolerability w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 17 publications
7
35
0
Order By: Relevance
“…Therefore, they are hydrolyzed into asiatic acid and madecassic acid by β-glycosidase, then these aglycones exert biological functions. The plasma concentration-time curve reflects that asiaticoside and madecassoside reach Tmax within 1–2 h after oral administration, while their metabolites asiatic acid and madecassic acid reach Tmax within 3 h, and accompanied by downward trend of parent compound ( Songvut et al, 2019 ). Madecassoside was considered to be a substrate of efflux transporters, which may influence the drug absorption in the gastrointestinal tract.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, they are hydrolyzed into asiatic acid and madecassic acid by β-glycosidase, then these aglycones exert biological functions. The plasma concentration-time curve reflects that asiaticoside and madecassoside reach Tmax within 1–2 h after oral administration, while their metabolites asiatic acid and madecassic acid reach Tmax within 3 h, and accompanied by downward trend of parent compound ( Songvut et al, 2019 ). Madecassoside was considered to be a substrate of efflux transporters, which may influence the drug absorption in the gastrointestinal tract.…”
Section: Resultsmentioning
confidence: 99%
“…In humans, the extract is metabolized to triterpenic acid metabolites by b-glycosidases from gut microbiota, which directly hydrolyse the glycosidic bonds of plant glycosides (Rowland et al 2018); therefore, the constituents derived from the extract in the human blood circulation were triterpenoid glycosides as the parent compounds (madecassoside and asiaticoside), and triterpenic acid metabolites (madecassic acid and asiatic acid). Following the oral administration of ECa 233 at 250 mg/kg dose for 7 days, the C max ratio in plasma between madecassoside and madecassic acid was approximately 1:10, whereas that between asiaticoside and asiatic acid was approximately 1:9; thus, triterpenic acid metabolites have considerably higher plasma concentrations than the parent compounds in humans (Songvut et al 2019).…”
Section: Discussionmentioning
confidence: 96%
“…50% of the consumed doses of the parent compounds) but scarcely in plasma and organ tissues (Anukunwithaya et al 2017b). In humans, a large amount of these metabolites was found in the plasma according to LC-MS/MS system analysis (Songvut et al 2019). Some studies of C. asiatica extract have shown that triterpenic acid metabolites have an effect on learning and memory via the neuroprotective and anxiolytic activities (Nasir et al 2011;Sirichoat et al 2015;Chaisawang et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…To explore the safety and tolerability of standardized extract of ECa233, oral doses of ECa233 were given to healthy Thai volunteers (250 and 500 mg). The volunteers tolerated the ECa233 well and did not discontinue the study due to serious adverse effects [24]. The extensive data on ECa233 is favorable in terms of the safety profile and thus, warrants the main interest in this beneficial extract for human use.…”
Section: Figurementioning
confidence: 91%